Mass Balance Analysis of Integrated Municipal Solid Waste Management: The Jakarta Recycle Center Program Case Study - Budiharto, Wikan Indrianingdyah; Martono , Dwi Nowo; Wahyuno, Sri (Future Science / FSH-PH Publications, 2023)
With the amount of waste increasing and landfill space becoming critical, the government has undertaken numerous measures to reduce waste, including creation of Integrated Solid Waste Management system through Jakarta Recycle Centre (JRC) Program. An integrated and sustainable waste management system will depend on both the physical and the governance components, with the physical aspect focusing on technical problems. To evaluate the physical aspect of JRC, the flow of the waste needs to be monitored and evaluated to see the success of waste separation and recycling system. This study employs mass balance analysis using data of waste in JRC facilities from January to December 2022. According to the study's findings, JRC system has a significant recycling rate which is around 46,43%. To improve the recycling rate, communication to residents about waste sorting process need to be enhanced. In order to reduce residue from sorting outcomes, it is also crucial to increase the ability and expertise of personnel in waste sorting.